35 x skulpturen. - Pas, Johan (Knokke : Vera Van Laer Gallery, 1991)
Armitage, Kenneth ; Asensi, Enrique ; Balderi, Iginio ; Van Braeckel, Malou ; Caro, Anthony ; Cavaliere, Alik ; Chia, Sandro ; Couturier, Marc ; Cucchi, Enzo ; Decock, Gilbert ; Fauville, Daniel ; Ghysels, Jean-Pierre ; Gilles, Stéphan ; Hepworth, Barbara ; Kounellis, Jannis ; De Loose, Joz. ; Paladino, Mimmo ; Pan, Marta ; Parmiggiani, Claudio ; Quilici, Pancho ; Rickey, George ; Riera i Arago, Josep ; De Smet, Yves ; Snauwaert, Jef ; Van Soom, Luk ; Tapta ; Verstockt, Mark ; Viard, Etienne
biografie
35 x skulpturen, Vera Van Laer Gallery, Knokke ; La Réserve, Knokke, 23 juni - 25 augustus 1991
Nederlands & Frans
boek